The Effect of Liquidity, Leverage, Company Size and Fixed Asset Intensity on Tax Aggressiveness - Khasanah, Lukluul; Nugroho, Wawan Sadtyo; Nurcahyono, Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
Tax is one of the primary sources of revenue in Indonesia. Optimization of tax revenue has many obstacles, one of which is the form of non-compliance in tax payments, called tax planning. This study aims to analyze the relationship of liquidity, leverage, company size and fixed asset intensity to tax aggressiveness in companies. The population of this study is manufacturing companies listed on the IDX using the purposive sampling method. The results showed that liquidity, leverage and company size affected tax aggressiveness, while fixed asset intensity did not affect tax aggressiveness. This research contributed to the development of the tax aggressiveness literature. Then, it has implications for the development of models in curbing tax aggressiveness carried out by companies.